THE EFFECT OF INTERNAL ENVIRONMENT AND INNOVATION STRATEGY ON COMPANY PERFORMANCE - Deri Prayudi; Irwan Nopian Sinaga; Taufik Risal (SEAN Institute, 2023)
PT. Abul Abul Bandung is a company engaged in the manufacture of shoes. Problems at PT. Abul Abul Bandung, namely not achieving the production target set by the company. This is allegedly due to machine damage during production activities and the lack of awareness and sense of responsibility of employees for the company's goals. The purpose of this study was to find out how much influence the internal environment has on company performance and find out how much influence innovation strategy has on company performance in PT. Abul Abul Bandung. The objects in this study are the internal environment (X1), innovation strategy (X2) and company performance (Y). The method used in this research is a quantitative method with a descriptive and associative approach. The sampling technique in this study used a saturated sampling (census). The samples taken in this study were 35 people, namely the leadership of PT. Abul Abul Bandung consisting of managers and supervisors. The data analysis technique used is multiple linear regression analysis, including the coefficient of determination test, multiple correlation coefficient, simultaneous test (F test) and partial test (T test). Based on the results of the study, it was found that there was a positive and significant influence of internal environmental variables on company performance of 0.751, and a positive and significant influence of innovation strategy variables on company performance variables of 0.956, as well as a positive and significant influence of internal environment and innovation strategies in improving performance company of 0.984 or 96.8% while the remaining 0.32 or 3.2% is influenced by other factors outside of this study. From these results it is known that there is a positive and significant influence of internal environment variables and innovation strategy variables in improving company performance.